Development of inclusive strategies in the value chain of extractive products: The Case of Tucumã (Astrocaryum Vulgare Mart.) negotiated by the D’Irituia cooperative with a cosmetics company - de Souza, Raimundo Renato Coelho; Gomes, Sérgio Castro; Bahia, Pablo Queiroz (Seven Editora, 2023)
The objective of this work is to analyze the production processes, product quality, and environment preservation developed by the small producers of Cooperativa D’Irituia to include themselves as suppliers of Tucumã (Astrocaryum Vulgare Mart.) sold with the cosmetics company Natura. The theoretical approach used in the study was the development of a value chain for agricultural and extractive products. Semi-structured interviews with directors and cooperative members were carried out to gather data and information from producers, which made it possible to understand the strategies developed for cultivation, management, collection, commercialization, the level of maturity of production, and the commercial relationship with the company. The results show evidence of inclusive aspects that enabled the inclusion of small producers and service providers in the production chain, leading them to earn income. The relationship with the large company encouraged cooperation, environmental preservation, and local development DOI: https://doi.org/10.56238/devopinterscie-015